2019
DOI: 10.1177/1455072519882784
|View full text |Cite
|
Sign up to set email alerts
|

Interaction rituals in an open drug scene

Abstract: Aims: Open drug scenes can be found in most major cities in Europe. Despite often being closed down by the police, the drug community continues to exist, and the drug scenes reappear elsewhere. There seem to be forces that hold these communities together, regardless of the substances used. In this study we explore whether interaction rituals have an impact on the decision by people to stay in the drug scene or to return after quitting their drug use. Method: In this ethnographic study, one of the researchers s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Research has shown, however, that there is an internal order to these open drug scenes that "regulates" relations between PWUD (Grønnestad et al, 2020). That was the case here, where the earliest dwellers came together as a group of "elders" who regulated the internal life of La Colline.…”
Section: Space Organized By Pwudmentioning
confidence: 78%
“…Research has shown, however, that there is an internal order to these open drug scenes that "regulates" relations between PWUD (Grønnestad et al, 2020). That was the case here, where the earliest dwellers came together as a group of "elders" who regulated the internal life of La Colline.…”
Section: Space Organized By Pwudmentioning
confidence: 78%
“…Investigating an inner-city drug scene in Oslo, Grønnestad et al (2020) illustrate how interaction rituals can provide the individual with an experience of group cohesion and increased emotional energy. Friedman et al (2015) have identified caring behaviours amongst people who inject drugs (PWID) that they interpret as expressions not only of solidarity but even altruism.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time as violence seems to constitute an extensively occurring and widely established social characteristic of drug scenes, a growing body of relatively recent research suggests the simultaneous existence of community-oriented norms and behaviours within drug subcultures. These embrace mutual support of people using drugs such as the provision of injection assistance, inspired by both prosocial and self-serving motivations (Brothers et al, 2020) and daily interaction rituals that promote social bonds and solidarity (Grønnestad et al, 2020). Further research states varying levels of community-minded norms and actions (Lalander, 2003;Stallwitz, 2012Stallwitz, , 2018aStallwitz, , 2018b) and both the presence (Friedman et al, 2015) and the absence of altruistic conduct concerning the prevention of infections due to needle sharing (Sandøy, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The rules and rituals in a drug scene can provide members with emotional energy and a sense of belonging. The ethnographic study by Trond Grønnestad, Hildegunn Sagvaag, and Philip Lalander explore how these interaction rituals also make it hard to leave the drug scene, and why those who manage to leave often return ( Grønnestad et al, 2020 ).…”
Section: Services Lifestyles and Use Ritualsmentioning
confidence: 99%